2016
DOI: 10.1182/blood-2016-01-693705
|View full text |Cite|
|
Sign up to set email alerts
|

Adult human megakaryocyte-erythroid progenitors are in the CD34+CD38mid fraction

Abstract: • Purification strategies developed for human Mk-E progenitors, as well as committed Mk and E progenitors.• MYB regulates the biphenotypic fate decision of human MEPs.Bipotent megakaryocyte/erythroid progenitors (MEPs) give rise to progeny limited to the megakaryocyte (Mk) and erythroid (E) lineages. We developed a novel dual-detection functional in vitro colony-forming unit (CFU) assay for single cells that differentiates down both the Mk and E lineages (CFU-Mk/E), which allowed development and validation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
79
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(83 citation statements)
references
References 40 publications
3
79
1
Order By: Relevance
“…While our work still supports a model for progressive restriction of developmental potential, it suggests that these events are clonally heterogeneous and occur much earlier in the hematopoietic hierarchy, in line with recent data 7,8,14,16 . Though our data fail to provide any evidence for CMP or MEP fates in situ , many experiments have provided evidence for MEP-like cells at a clonal level 4,12,13,24 . We posit that while Mk-Er bipotential exists in transplant or culture setting, this fate is not substantially manifested in unperturbed conditions.…”
contrasting
confidence: 93%
See 1 more Smart Citation
“…While our work still supports a model for progressive restriction of developmental potential, it suggests that these events are clonally heterogeneous and occur much earlier in the hematopoietic hierarchy, in line with recent data 7,8,14,16 . Though our data fail to provide any evidence for CMP or MEP fates in situ , many experiments have provided evidence for MEP-like cells at a clonal level 4,12,13,24 . We posit that while Mk-Er bipotential exists in transplant or culture setting, this fate is not substantially manifested in unperturbed conditions.…”
contrasting
confidence: 93%
“…1d–e and Extended Data Fig. 4b) 12,13 . At 8 weeks, our analysis revealed the activity of a set of multilineage clones (239±58), with lymphoid (B), My and Er contribution, but still with no presence in Mk, indicating the existence of Mk-deficient lympho-erythromyeloid (LEM) progenitors (Fig.…”
mentioning
confidence: 91%
“…While not widely appreciated, all hematopoietic stem cells and most hematopoietic progenitor cells (including multi potent progenitor (MPP) and common myeloid progenitor (CMP), but excluding committed erythroid progenitors) express MPL, the receptor for TPO, on their cell membranes. [5, 1013]…”
Section: Megakaryopoiesis and Erythropoiesismentioning
confidence: 99%
“…However, early experiments by Debili et al found dual-lineage (Mk and erythroid) colonies composed of 100 to 1,000 erythroblasts intermixed with a few MK that were enriched in the CD34+CD38+/− and CD34+CD38− cell fractions. Even though CD34+CD38high human cells have been published as being greatly enriched for erythroid committed cells,[10] papers still use this gate to isolate what they refer to as human “MEP.” Consequently, single cell RNA sequencing data from this population shows that many of these cells are erythroid committed, which would lead investigators to question the existence of human MEPs. [27, 28]…”
Section: Challenges In Isolating Mepmentioning
confidence: 99%
“…As summarized in Table 1, MEPs have been characterized using a combination of cell surface markers including IL-3R, FLT3, MPL (assessed using BAH1 clone and other antibodies), CD36, CD41, CD71 and CD105 (8*, 9*, 10**, 14**). Using a combination of approaches including functional, single cell transcriptomics and lineage potential assays, these studies reveal that the identification of MEP and their subpopulations appears highly dependent on gating strategy; this likely reflects their extensive heterogeneity.…”
Section: Isolation and Characterization Of Megakaryocyte-erythroid Anmentioning
confidence: 99%